Mechanism and Pharmacodynamic Substance Basis of Raw and Wine-Processed Evodia rutaecarpa on Smooth Muscle Cells of Dysmenorrhea Mice - Yeqian Liu; Hong Li; Lei Chen; Hongxia Zhao; Jian Liu; Shan Gong; Danfeng Ma; Chunming Chen; Shuiqing Zeng; Hongping Long; Weiqiong Ren (Pain Research and Management)
Objectives. Evodia rutaecarpa (ER) is a well-known herbal Chinese medicine traditionally used for analgesia in dysmenorrhea, headaches, abdominal pain, etc. Notably, the analgesic effect of wine-processed Evodia rutaecarpa (PER) was more potent than that of raw ER. This research aimed to investigate the mechanism and pharmacodynamic substance basis of raw ER and PER on smooth muscle cells of dysmenorrhea mice. Methods. Metabolomics methods based on UPLC-Q-TOF-MS were utilized to analyse the differential components of ER before and after wine processing. Afterwards, the uterine smooth muscle cells were isolated from the uterine tissue of dysmenorrhea and normal mice. The isolated dysmenorrhea uterine smooth muscle cells were randomly divided into four groups: model group, 7-hydroxycoumarin group (1 mmol/L), chlorogenic acid (1 mmol/L), and limonin (50 μmol/L). The normal group consisted of the isolated normal mouse uterine smooth muscle cells, which were repeated 3 times in each group. The cell contraction and the expression of P2X3 and Ca2+ in vitro were determined using immunofluorescence staining and laser confocal; ELISA was used for detection of PGE2, ET-1, and NO content after 7-hydroxycoumarin, chlorogenic acid, and limonin administered for 24 h. Results. The metabolomics results suggested that seven differential compounds were identified in the extracts of raw ER and PER, including chlorogenic acid, 7-hydroxycoumarin, hydroxy evodiamine, laudanosine, evollionines A, limonin, and 1-methyl-2-[(z)-4-nonenyl]-4 (1H)-quinolone. The in vitro results showed that 7-hydroxycoumarin, chlorogenic acid, and limonin were able to inhibit cell contraction and PGE2, ET-1, P2X3, and Ca2+ in dysmenorrhea mouse uterine smooth muscle cells and increase the content of NO. Conclusion. Our finding suggested that the compounds of the PER were different from those of the raw ER, and 7-hydroxycoumarin, chlorogenic acid, and limonin could improve dysmenorrhea in mice whose uterine smooth muscle cell contraction was closed with endocrine factors and P2X3-Ca2+ pathway.